Targeting delivery of liposomes with conjugated p-aminophenyl-α-d-manno-pyranoside and apolipoprotein E for inhibiting neuronal degeneration insulted with β-amyloid peptide. (February 2015) - Kuo, Yung-Chih; Lin, Che-Yu
Abstract Liposomes with conjugated p-aminophenyl-α-d-manno-pyranoside (APMP) and apolipoprotein E (ApoE) (APMP-ApoE-liposomes) were employed to carry neuron growth factor (NGF) across the blood–brain barrier (BBB) and enhance the survival of degenerated neurons. APMP-ApoE-liposomes were used to deliver NGF across a monolayer of human brain-microvascular endothelial cells (HBMECs) regulated by human astrocytes (HAs) for rescuing SK-N-MC cells from an insult of β-amyloid peptide 1–42 (Aβ1–42). An increase in the APMP concentration enhanced the particle size, HBMEC and HA viability, permeability for propidium iodide (PI), and permeability for NGF, however, reduced the absolute value of zeta potential, APMP conjugation efficiency and transendothelial electrical resistance (TEER). In addition, an increase in the ApoE concentration increased the particle size, absolute value of zeta potential, HBMEC and HA viability, permeability for PI, permeability for NGF and SK-N-MC cell viability, however, decreased the ApoE conjugation efficiency and TEER. APMP and ApoE on liposomes can be promising surface moieties to carry NGF across the BBB, target degenerated neurons and inhibit Aβ1–42-induced neurotoxicity in Alzheimer's disease.